Faktor-Faktor yang Memengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Kendaraan Bermotor di Kota Denpasar - Krisnadeva, Anak Agung Ngurah; Lely Aryani Merkusiwati, Ni Ketut (E-Jurnal Akuntansi, 2020)
This study aims to obtain empirical evidence about the influence of taxpayer income levels, taxpayer awareness, service quality, and tax penalties on tax compliance in paying motor vehicle tax in Denpasar. The theory used is behavioral accounting theory as grand theory and attribution theory as supporting theory. The population is all active PKB taxpayers registered at the Joint Office of SAMSAT Denpasar City totaling 713,601. The research sample of 100 respondents was calculated based on the Slovin formula with the accidental sampling method. Data collection by questionnaire method and documentation technique. The data analysis technique is multiple linear regression analysis. The results showed the level of taxpayer income, taxpayer awareness, service quality and tax penalties had a positive effect on taxpayer compliance in paying motor vehicle tax in Denpasar. Keywords: Income Levels; Awareness; Service Quality; Tax Penalties; Motor Vehicle Taxpayer Compliance.